(untitled) (Research, Society and Development, 2020)
Objective: Describe the users’ perception of nursing actions in sexual and reproductive health care. Method: a descriptive study with a qualitative approach, carried out in a specialized service of regional reference in Reproductive and Sexual Health Care in the State of Ceará. Twenty people participated in the study, being users, nurses and informants. Semi-structured interviews and systematic observation were used for data collection, with thematic content analysis. Results: it is evident that the relationship of participants with nurses in care related to reproductive planning is linked due to information and more comprehensive care. It is observed that the availability of contraceptive methods offered is insufficient in view of the users’ demand. The attitudes and behaviors for reproductive health have weaknesses in care. Satisfaction with care is related to the information passed on in nursing care. Final considerations: Health care has a fragmented configuration due to limited services and educational processes. In its care limits, nursing offers expanded care in its daily practices.